2018
DOI: 10.1097/ijg.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Macular and Multifocal PERG and FD-OCT in Preperimetric and Hemifield Loss Glaucoma

Abstract: PERG and OCT parameters may be abnormal, with significant correlations between measurements, in PG eyes. Both technologies may be useful for detection of early glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…There is compelling evidence to support the notion that the mfPERG response originates from activity of inner-retinal neurons and is likely generated at the optic nerve head [ 45 , 46 ]. While multiple studies have demonstrated the reduction of mfPERG amplitude in several disease conditions, its ability to detect focal defects as opposed to a generalised reduction may be disease specific [ 45 , 47 – 52 ].…”
Section: Electrophysiological Tests Of Optic Nerve and Retinal Ganglion Cell Functionmentioning
confidence: 99%
“…There is compelling evidence to support the notion that the mfPERG response originates from activity of inner-retinal neurons and is likely generated at the optic nerve head [ 45 , 46 ]. While multiple studies have demonstrated the reduction of mfPERG amplitude in several disease conditions, its ability to detect focal defects as opposed to a generalised reduction may be disease specific [ 45 , 47 – 52 ].…”
Section: Electrophysiological Tests Of Optic Nerve and Retinal Ganglion Cell Functionmentioning
confidence: 99%
“…19 Thus, use of PERG has been proposed for evaluating SF relationship in some recent studies. Kreuz and coworkers 211 reported a significant correlation between the steadystate latency and P50 peak time on PERG and macular RNFL thickness. This finding was confirmed by Park and coworkers 305 who showed that a linear regression model (r 2 = 0.22) best fitted the relationship between N95 amplitude on PERG and GCIPL thickness.…”
Section: Relationship Of Macular Parameters and Other Functional Measures-a Fewmentioning
confidence: 96%
“…5,6 Several studies have used variants of the pattern electroretinogram (PERG), a sensitive measure of RGC function, [7][8][9] to investigate local responses in healthy and diseased central retina. [10][11][12][13][14][15][16][17][18][19][20][21] It is still not well-established whether the magnitude of the PERG signal reflects the magnitude of RGC density at multiple locations, whether PERG latency reflects the conduction time of intraretinal axons, and whether local PERGs have unique features that may provide clues on regional RGC vulnerability in optic nerve disease, such as glaucoma and optic neuritis.…”
Section: Introductionmentioning
confidence: 99%